Microstructure, coercivity and thermal stability of nanostructured (Nd, Ce)-(Fe, Co)-B hot-compacted permanent magnets. (15th August 2022) - Wu, Yuye; Skokov, Konstantin P.; Schäfer, Lukas; Maccari, Fernando; Aubert, Alex; Xu, Hao; Wu, Haichen; Jiang, Chengbao; Gutfleisch, Oliver
Abstract: We report on microstructure, hard magnetic properties and thermal stability of nanocrystalline (Nd0.85 Ce0.15 )15 (Fe1- x Co x )78 B7 ( x = 0 – 1) hot-compacted permanent magnets. At lower Co concentrations ( x < 0.3), the substitution of Fe by Co changes the composition of grain boundary phase from non-magnetic (Nd, Ce)2 Fe1 to magnetic (Nd, Ce)1 (Fe, Co)2, leading to the degrading of the coercivity. At x ≥ 0.6, the grain boundary phase is no longer observed between the nanocrystalline grains, resulting in strong magnetic coupling of constituent phases. With the further increase of Co concentration ( x >0.6), additional RE(Fe, Co)2, RE(Fe, Co)4 B and RECo5 phases are gradually formed in the magnets. A new type of microstructure with nanograins of RE2 (Fe, Co)14 B phase, RE(Fe, Co)2 phase and RE(Fe, Co)4 B phase, with partial or without grain boundary phase shows good thermal stability ( x = 0.4 and 0.6). In (Nd0.85 Ce0.15 )15 (Fe0.4 Co0.6 )78 B7 magnets, the absolute values of temperature coefficient of coercivity | β | can reach 0.3 %/K within the temperature range of 300 K - 500 K, and it exceeds 0.23 %/K for the temperature range of 300 K - 650 K, indicating a promising method for designing highly thermal stable permanent magnets. Graphical abstract: Image, graphical abstract